2015
DOI: 10.1098/rsif.2015.0627
|View full text |Cite
|
Sign up to set email alerts
|

A simple mechanistic explanation for original antigenic sin and its alleviation by adjuvants

Abstract: A large number of published studies have shown that adaptive immunity to a particular antigen, including pathogen-derived, can be boosted by another, cross-reacting antigen while inducing suboptimal immunity to the latter. 0912458109)). Here, focusing on the humoral aspects of adaptive immunity, I propose a simple and testable mechanism: that OAS occurs when T regulatory cells induced by the first antigen decrease the dose of the second antigen that is loaded by dendritic cells and available to activate naive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…In conclusion, our findings are consistent with other studies that point to negative and positive interference as a mechanism affecting this enhancement of cross-reactivity after sequential immunization[9–11,31]. Therefore, immunization regimens that can relieve negative interference while increasing positive interference (especially to conserved regions on an antigen) may act to broaden cross-reactive immunity to the Influenza virus[15,32].…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, our findings are consistent with other studies that point to negative and positive interference as a mechanism affecting this enhancement of cross-reactivity after sequential immunization[9–11,31]. Therefore, immunization regimens that can relieve negative interference while increasing positive interference (especially to conserved regions on an antigen) may act to broaden cross-reactive immunity to the Influenza virus[15,32].…”
Section: Discussionsupporting
confidence: 92%
“…Whether antibodydependent mechanisms may also suppress T cell responses to influenza, as described in other virus models, is an area requiring further research [49]. The preferential induction or recruitment of regulatory cells upon re-exposure has been proposed as an explanatory mechanism for original antigenic sin responses and may also contribute to antagonistic T cell responses with repeat influenza vaccination [50]. There is evidence from animal studies that repeated vaccination can interfere with the development of cross-reactive immunity against other subtypes, likely mediated by reduced virusspecific CD8+ T cell response [51,52].…”
Section: Possible Immune Mechanisms For Repeated Vaccination Effectsmentioning
confidence: 99%
“…Most influenza vaccines are derived from egg-adapted high-growth reassortant viruses, and the contribution of egg-induced mutations to repeated vaccination effects should be elucidated. In addition, animal and computational investigations suggest that some adjuvanted vaccines may reduce or eliminate original antigenic sin effects [50,57,58]. Additional research is needed to understand mechanisms and determine if this may be observed in a sustainable way in humans.…”
Section: Five-year Viewmentioning
confidence: 99%
“…27 It is possible that pre-existing immunity to B strains other than B/Massachusetts/02/2012 negatively affected the immune response to the B/Massachusetts/02/2012 strain; this phenomenon is called original antigenic sin. 28,29 For example, a previous study assessing the prime-boost responses following a change in the 2 B lineages (B/Yamagata and B/Victoria) reported the influence of original antigenic sin on responses to B strains; repeated administration of the annual trivalent influenza vaccine containing the B/Victoria lineage antigen strongly recalled antibodies to the B/Yamagata antigen after the first exposure, but elicited lower B/Victoria responses. 30 In Japan, a mixed epidemic of B/Victoria and B/Yamagata was observed during the 2011/2012 and 2012/2013 seasons.…”
Section: Discussionmentioning
confidence: 99%